Analysis of ADL and Its Affect Factors for 605 Individuals with Burn Injury - Dan TANG; Kuicheng LI; Haiyan CAO; Cecilia W P Li-Tsang; Yueqing LIN; Ya'nan FENG; Chuanshun LIU; Xiaoyan LIU (康复学报)
Objective:To explore the effect of rehabilitation on activity of daily living(ADL)for individuals with burn injury and to identify the affect factors and predictive factors.Methods:605 inpatient individuals with burn injury were recruited in the study. The personal factors, medical factors, treatment factors, and the abilities of daily living(by MBI and FIM)were collected. A paired sample t-test was applied to compare the MBI score and FIM score before and after rehabilitation. Liner regression was used to identify the affect factors and predictive factors.Results:The MBI score and FIM score were improved significantly after rehabilitation (P<0.001). Family financial situation, payer source, area of burn(TBSA), depth of burn, regions of burn, rehabilitation treatment duration, and length of stay(LOS)were related with MBI score before discharge(all P<0.05). TBSA, rehabilitation treatment duration, work-related burn, LOS and social insurance funding were found to be the predictive factors of MBI score. Similarly, family financial situation, payer source, reason of burn, TBSA, depth of burn, regions of burn, rehabilitation treatment duration, and LOS were related with FIM score before discharge(all P<0.05). And TBSA, rehabilitation, work-related burn, and LOS were found to be the predictive factors of FIM score.Conclusion:Individuals with burn injury can benefit from rehabilitation intervention in performance of ADL. Many factors may affect the abilities of daily living but area of burn, rehabilitation treatment duration and LOS are the predictors. Early and enough comprehensive rehabilitation intervention for burn patients is highly recommended.